Factors associated with adolescent pregnancy among girls aged between 15 and 19 years in Muhanga district, Rwanda - Isaie Nshimiyimana; Mochama Monica; Amos Habimana (BMC Public Health)
Abstract Background Adolescent pregnancy, also known as teenage pregnancy, is an unwanted pregnancy affecting girls aged 15–19 years. With a global prevalence of 25%, Africa has 18.8% of female adolescents become pregnant, preventing them from a better standard of living, such as good education and parental care, and adolescent pregnancy, which poses health risks, educational and career disruptions, financial strain, and lower academic achievement, while also increasing public costs and social service demand. This study aimed to determine the prevalence and factors associated with adolescent pregnancy among girls aged 15–19 years in Muhanga district, Rwanda. Methods The study involved 392 female adolescents aged 15–19 years in Muhanga district, Rwanda. The participants were selected through a multistage sampling method, and the study ensured voluntary participation whereby the assent and consent forms were signed. Data were collected through questionnaires and analyzed via STATA v.18, and statistical analysis, including chi-square tests and multivariate logistic regression, was used to control for confounders. Ethical approval was obtained from Mount Kenya University and Muhanga district administration. Results The study reported an adolescent pregnancy rate of 10.7% (95% CI: 7.7–13.7). Adolescents financially supported by others (not their parents or guardians) had higher odds of having pregnancy (AOR = 3.9, 95% CI: 1.431–10.467, p < 0.01). Those not in school and primary school showed higher odds of having a pregnancy (AOR = 23.76, 95% CI: 6.833–82.630, p < 0.001) and (AOR = 25.60, 95% CI: 7.224–90.741, p < 0.001), respectively, compared to those in secondary school. Receiving SRH education was associated with lower odds of having a pregnancy (AOR = 0.2, 95% CI: 0.80–0.514, p < 0.001). Experiencing peer pressure increased the odds of having a pregnancy (AOR = 4.12, 95% CI: 1.521–11.131, p < 0.01). Conclusions This study highlights a significant adolescent pregnancy rate in Muhanga district, emphasizing the need for targeted interventions. Addressing educational gaps, improving financial support systems, and enhancing sexual and reproductive health education are crucial steps. Policymakers should focus on these areas to reduce adolescent pregnancies and improve outcomes for young girls. Future efforts should also include strategies to counteract peer pressure and integrate comprehensive support programs.